Heat Treatment Effect on Anodizing Corrosion Resistance of Low Carbon Steel - Ajeel, Sami A. (Nahrain University College of Engineering Journal, 2017)
This work involves studying heat treatment effect on anodized low carbon steel using electrochemical measurements. Heat treatments of low carbon steel before anodizing were applied by anodizing at different temperatures of 650, 900, and1000°C for one hour. Anodizing process was used for non-annealed and annealed low carbon steel at the above temperatures in KOH solution.The electrochemical behavior of low carbon steel, anodized low carbon steel, and anodized annealing low carbon steel at the above temperatures in 3.5 wt% NaCl solution using potentiostat device. Corrosion rates for the above conditions were measured. The corrosion rates measured results indicate an improvement in corrosion resistance of anodized annealing low carbon steel. Surface characterization of anodic film on low carbon steel was examined anodic film on low carbon steel using Atomic force microscopy (AFM) and optical microscopy used to examine the specimens before and after corrosion test. the practical results indicate the best conditions to obtain higher corrosion resistance are for anodized low carbon steel annealed the steel before anodizing at 1000 °C.